Body mass index, perceived and actual physical competence: the relationship among young children. Issue 6 (30th November 2012) - Spessato, B. C.; Gabbard, C.; Robinson, L.; Valentini, N. C.
Abstract Background The purpose of this study was to examine the relationship between perceived physical competence (PPC), actual motor competence (MC) and body mass index (BMI) in young children. Methods We assessed MC (Test of Gross Motor Development – 2nd Edition), PPC (Pictorial Scale of Perceived Competence and Social Acceptance) and BMI (CDC calculator) of 178 young children ages 4–7 years. Results The linear regression model for the overall sample showed that BMI was a better predictor of PPC than MC. Also, obese children had lower PPC, but showed no differences in MC compared with leaner peers. Conclusions PPC of young obese children was lower than their leaner counterparts, yet their MC was similar. That outcome draws attention to the importance of promoting positive PPC in young children.